2016
DOI: 10.2147/opth.s111648
|View full text |Cite
|
Sign up to set email alerts
|

Direct ophthalmoscopy on YouTube: analysis of instructional YouTube videos’ content and approach to visualization

Abstract: BackgroundDirect ophthalmoscopy is well-suited for video-based instruction, particularly if the videos enable the student to see what the examiner sees when performing direct ophthalmoscopy. We evaluated the pedagogical effectiveness of instructional YouTube videos on direct ophthalmoscopy by evaluating their content and approach to visualization.MethodsIn order to synthesize main themes and points for direct ophthalmoscopy, we formed a broad panel consisting of a medical student, junior and senior physicians,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…For teaching direct ophthalmoscopy, Borgersen and colleagues systematically evaluated the effectiveness of instructional YouTube videos on direct ophthalmoscopy by evaluating their content and approach to visualization. 5 Their group provided the following suggestions for videos instructing in direct ophthalmoscopy: (1) illustrate the key themes and points essential for performing direct ophthalmoscopy; (2) consider how to illustrate the key concepts so that the learner sees what he/she should expect to see; (3) put emphasis on how to examine the fundus and interpret findings; (4) consider omitting irrelevant details, highlighting essential information, and presenting words and pictures in combination. 5 …”
Section: Ophthalmology-specific Virtual Teaching Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…For teaching direct ophthalmoscopy, Borgersen and colleagues systematically evaluated the effectiveness of instructional YouTube videos on direct ophthalmoscopy by evaluating their content and approach to visualization. 5 Their group provided the following suggestions for videos instructing in direct ophthalmoscopy: (1) illustrate the key themes and points essential for performing direct ophthalmoscopy; (2) consider how to illustrate the key concepts so that the learner sees what he/she should expect to see; (3) put emphasis on how to examine the fundus and interpret findings; (4) consider omitting irrelevant details, highlighting essential information, and presenting words and pictures in combination. 5 …”
Section: Ophthalmology-specific Virtual Teaching Resourcesmentioning
confidence: 99%
“…An advantage of social media is the visual nature of ophthalmology, offering a unique platform for educational image sharing. Borgerson et al 5 Evaluated the effectiveness of instructional YouTube videos on direct ophthalmoscopy by evaluating their content and approach to visualization. Devitt et al 9 Evaluated an ophthalmology computer aided learning (CAL) program for medical students and found that students in the control group showed no improvement over the test period, whilst the students who had access to CAL significantly increased their knowledge base.…”
Section: Ophthalmology-specific Virtual Teaching Resourcesmentioning
confidence: 99%
“…This can range from high fidelity (e.g., mannequins) to low fidelity (e.g., mock cases in an empty patient room). 118 Technology can facilitate these simulations by using stored images or videos, as well as a number of simulation smartphone apps.…”
Section: Incorporating Technologymentioning
confidence: 99%
“…Borgersen et al 20 described the possible use of YouTube video lessons along with traditional theoretical lessons, since different instructional videos have been widely used in the past to aid in the guidance of general physical examination and basic medical skills. Problems with this method included lack of sufficient video lessons, low-quality videos and absence of long-term comparison studies.…”
Section: Resultsmentioning
confidence: 99%